Analysis of Verification Aspects Associated with the Return of BPJS Health Claims for Inpatients at RSU Surya Husadha Denpasar: Analisis Aspek-Aspek Verifikasi yang Berhubungan dengan Pengembalian Klaim BPJS Kesehatan Pasien Rawat Inap di RSU Surya Husadha Denpasar - Yunawati, Ni Putu Linda; Aridayana, I Putu Mega; Faidah, Nurul; Murcittowati, Putu Ayu Sri (Universitas Muhammadiyah Sidoarjo, 2025)
Submission of claims by hospitals to the Social Security Agency (BPJS) Health will go through a verification process and requires compliance with verification aspects. However, they often experience refunds or delays in payments due to non-compliance with established regulations. This results in negative impacts such as disruption to hospital cash flow, increased workload, and failure to achieve service quality indicators. It is necessary to have claim data ready before submitting a claim by the hospital. The aim of this research is to determine the relationship between aspects of membership administration, service administration and health services with the return of BPJS Health claims. This type of research uses quantitative descriptive analysis with a cross sectional approach. This research was conducted on 145 pending claims selected using a simple random sampling technique. Based on the results of the discrepancy analysis in the aspects of membership administration, namely 6 files (4.1%), service administration, namely 103 files (71%), and health services, namely 36 files (24.8%). These three aspects of verification are related to the return of BPJS Health claims, resulting in a p-value = 0.000, meaning H0 is rejected. To increase efficiency and reduce the number of claim returns, it is necessary to carry out internal verification before claims are sent to BPJS Health.